2021
DOI: 10.3390/ijms222413509
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling in the Cerebellar Radial Glia and Its Association with Morphological Changes during Zebrafish Development

Abstract: Radial glial cells are a distinct non-neuronal cell type that, during development, span the entire width of the brain walls of the ventricular system. They play a central role in the origin and placement of neurons, since their processes form structural scaffolds that guide and facilitate neuronal migration. Furthermore, glutamatergic signaling in the radial glia of the adult cerebellum (i.e., Bergmann glia), is crucial for precise motor coordination. Radial glial cells exhibit spontaneous calcium activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Moreover, in Balh et al [ 69 ] study the neural circuits changes were evaluated using electrode-based imaging and calcium signaling. Calcium imaging of the zebrafish brain is yet another innovative technique assessing neural activity, recently described in a study regarding the cerebellar radial glia developmental patterns in zebrafish larvae by correlation to morphodynamic changes [ 69 ].…”
Section: Zebrafish Physiology Neurodevelopment and Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in Balh et al [ 69 ] study the neural circuits changes were evaluated using electrode-based imaging and calcium signaling. Calcium imaging of the zebrafish brain is yet another innovative technique assessing neural activity, recently described in a study regarding the cerebellar radial glia developmental patterns in zebrafish larvae by correlation to morphodynamic changes [ 69 ].…”
Section: Zebrafish Physiology Neurodevelopment and Behaviormentioning
confidence: 99%
“…Moreover, in Balh et al [ 69 ] study the neural circuits changes were evaluated using electrode-based imaging and calcium signaling. Calcium imaging of the zebrafish brain is yet another innovative technique assessing neural activity, recently described in a study regarding the cerebellar radial glia developmental patterns in zebrafish larvae by correlation to morphodynamic changes [ 69 ]. Furthermore, Zylberthal and Bianco [ 70 ] reported the calcium imaging technique combined with mechanistic network modelling in zebrafish larvae to evaluate spatial and temporal network interactions in the zebrafish optic tectum in response to visual stimuli (prey-catching responses).…”
Section: Zebrafish Physiology Neurodevelopment and Behaviormentioning
confidence: 99%
“…RG cells play a central role in the origin and placement of neurons [ 15 ] because their processes form structural scaffolds that guide and facilitate neuronal migration. In addition, glutamatergic signaling in the RG of the adult cerebellum (Bergmann glia) of zebrafish is critical for precise motor coordination [ 16 ]. Studies in zebrafish have shown that RG cells exhibit spontaneous calcium activity, and functional interaction propagates calcium waves.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in zebrafish have shown that RG cells exhibit spontaneous calcium activity, and functional interaction propagates calcium waves. However, the origin of calcium activity in relation to the ontogeny of cerebellar radial glia is just beginning to be explored, and results in zebrafish have elucidated important aspects of RG organization, morphology, and calcium signaling, emphasizing its role in complex behavioral paradigms [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the cross-reactivity of several antibodies directed against mammalian proteins also enabled the precise characterization of the neurogenic cells in the preoptic region of the adult zebrafish hypothalamus, highlighting the strong similarities, but also the differences in the neurogenic niches between mammals and fish. Pereida-Jaramillo et al [9] used transgenic fluorescent calcium sensors to visualize in vivo the transient calcium uptakes underlying the depolarization of neurons, and the membrane currents of glial cells whose function remains poorly understood. First, a calcium sensor expressed under the control of the glial gfap promoter was instrumental in demonstrating for the first time that rostro-caudal calcium waves occur in cerebellar Bergmann glial cells starting from 5 dpf.…”
mentioning
confidence: 99%